Faktor-Faktor yang Memengaruhi Foreign Direct Investment di Luar Jawa-Bali Tahun 2011 - 2020 - Rizqi Muzakki; Sukim Sukim (Politeknik Statistika STIS, 2022)
Sources of funding are the main obstacle in economic development in Indonesia. The government needs to find sources of financial assistance, including from abroad. Foreign direct investment (FDI) is a source of direct income from abroad in the form of investment. However, most of the incoming investment flows are centered in Java. One of the goals of the 2020-2024 National Medium-Term Development Plan (RPJMN) is to increase the distribution of investment flows between Java and outside Java. Therefore, this study aims to determine what variables affect FDI in areas outside Java-Bali. The research method used is the panel data regression method. Simultaneous test results show that the variables of GDP, inflation, HDI, labor, infrastructure, and exports together have an effect on FDI. Partially the variables that have a significant effect on FDI in areas outside Java-Bali are GRDP, inflation, HDI, and exports variables. Meanwhile, labor and infrastructure variables have no effect on FDI.